The Role of Non-Governmental Organization (NGO) in Advocating the National Security Bill - Djuyandi, Yusa (Jurnal Bina Praja: Journal of Home Affairs Governance, 2016)
The role run by a coalition of NGOs in advocating the National Security Bill aimed at encouraging the birth of national security policy to appropriate to the purpose of reform. However, until now the role of NGOs in advocating National Security Bill has not been able to encourage the authorities to reconstruct the draft of national security policy that is consistent with the objectives of security sector reform. This study is conducted to analyze the role of NGOs in the security sector reform in Indonesia, particularly through the advocacy of the National Security Bill. The method used in this study is a qualitative method. The result shows that NGOs, which are members of the KMSRK, have been running the multiple roles, such as: popularly involved in policy making, providing political education to the community, promoting or encouraging reform, and promoting the interests of the community. The study also suggests the existence of new findings of the role of NGOs, which is forming a coherent unity of interests.